Mild adverse childhood experiences increase neural efficacy during affective theory of mind. (2nd January 2018) - Vai, Benedetta; Riberto, Martina; Ghiglino, Davide; Bollettini, Irene; Falini, Andrea; Benedetti, Francesco; Poletti, Sara
Abstract: Adverse childhood experiences (ACEs) affect the development of social cognition (and identify a risk factor for several physical and mental disorders). Theory of Mind (ToM) is a key predictor of social functioning, mental health, and quality of life. No previous study explored the effect of mild ACEs on the neural correlates of ToM in healthy humans. In 23 healthy participants, we used brain blood oxygen level-dependent fMRI to study the effect of ACEs on the neural responses to tasks targeting affective and cognitive ToM. Results pointed out an association between ACEs and a lower neural response in the vermis of the cerebellum ( r  = −.85), precentral gyrus, and inferior frontal operculum (putative Mirror Neural System, r  = −.78) during affective ToM. A lower recruitment of these brain regions, paralleled by the same performance, could express an increased neural efficacy in inferring affective mental states driven by previous experience, in this case, ACEs.